Maternal Mortality in Klaten Regency (Determinant Factors Analysis) - Sesunan, Arfan Syahfani; Respati, Supriyadi Hari; Sulistyowati, Sri (Journal of Maternal and Child Health, 2021)
Background: Failure in reducing maternal mor